Mathematical Spatial Ability and Geometry Ability: A Correlation Study (International Journal of Scientific Research and Management (IJSRM), 2024)
Geometry is a mathematical content that requires students’ spatial reasoning. The difficulty experienced by students in solving geometry problems is because students do not understand spatiality and spatial visualization of three-dimensional shapes presented in two dimensions. This research is quantitative research with the main data of XII grade students. The selection of subjects is based on the three-dimensional material taught at the XII grade level. The purpose of this research is as an initial observation of the spatial correlation with students’ ability to solve three-dimensional problems. Spatial indicators in this study include spatial visualization, spatial orientation and spatial relations. The material of the third dimension is about the position of the point to the point, line and plane, the position of the line to the line and plane, the position of the plane to the plane and the distance of the line to the line and plane. The research method used is assisted by Ms.Excel to determine the correlation between spatial abilities with geometry skills of students and based on the calculation results obtained it can be concluded that there is a correlation between the spatial ability of students to the geometry ability of students in solving the three-dimensional material.